Rare earth antibacterial ultraviolet-proof composite material and preparation method thereof

By building a three-dimensional crosslinking network, using 2-vinyl-4,6-diamino-1,3,5-triazine to form coordination bonds with rare earth ions, the problem of easy agglomeration of rare earth antibacterial materials in composite materials is solved, and the synergy between efficient antibacterial and ultraviolet-proof functions is achieved, and the mechanical properties and thermal stability of the material are improved.

CN120329472AInactive Publication Date: 2025-07-18THIN MATERIAL TECHNOLOGY (BAOTOU) CO LTD +1

Patent Information

Application Number
CN202510815446.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-18
Publication Date
2025-07-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing rare earth antibacterial materials are prone to agglomeration in composite materials, resulting in a decrease in specific surface area, a decrease in mechanical properties, and poor functional synergy, making it difficult to achieve efficient antibacterial and ultraviolet ray protection at the same time.

Method used

A three-dimensional crosslinking network is constructed using 2-vinyl-4,6-diamino-1,3,5-triazine as functional monomers. The coordination bonds are formed with rare earth ions through amino and triazine ring nitrogen atoms, and the rare earth is anchored in the form of monodispersed or nanoclusters, bound to the polymer backbone, strengthen interface binding, and avoid phase separation through covalent bonding.

Benefits of technology

The monodispersion of rare earth ions on the polymer framework is achieved, interface binding is enhanced, aggregation and phase separation is avoided, and efficient antibacterial and broad-spectrum anti-ultraviolet functions are achieved, while improving the mechanical strength and thermal stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120329472A_ABST
    Figure CN120329472A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of antibacterial materials, in particular to a rare earth antibacterial ultraviolet-proof composite material and a preparation method thereof.The preparation method comprises the following steps that lanthanum oxide is added into a 1-2 mol / L dilute nitric acid solution, heating and stirring are conducted at the temperature of 60-80 DEG C till the lanthanum oxide is completely dissolved, a lanthanum ion solution is obtained, calcium nitrate tetrahydrate and the lanthanum ion solution are added into deionized water, a solution A is prepared, and the solution B is prepared; the preparation method comprises the following steps: adding diammonium hydrogen phosphate and a polymer carrier into deionized water to prepare a solution B, slowly dropwise adding the solution B into the solution A under magnetic stirring to obtain a turbid liquid, adjusting the pH value, stirring for 6-8 hours in an oil bath, standing and aging for 24-36 hours at room temperature, filtering to obtain a precipitate, washing and drying to obtain the rare earth antibacterial ultraviolet-proof composite material. The rare earth antibacterial and ultraviolet-proof composite material prepared by the invention has good antibacterial and ultraviolet shielding properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of antibacterial materials, and particularly relates to a rare earth antibacterial and ultraviolet - resistant composite material and a preparation method thereof. Background Art

[0002] Traditional antibacterial materials mainly rely on metal ions such as silver and copper or organic antibacterial agents, and have defects such as high cost, high environmental toxicity, and insufficient long - term stability. Ultraviolet - shielding materials mostly use inorganic nanoparticles such as titanium dioxide and zinc oxide. Although they have certain protective capabilities, their poor dispersibility, easy agglomeration, and single function make it difficult to meet the requirements of the multifunctional synergistic performance of materials in complex scenarios. Rare earth antibacterial materials can achieve long - term antibacterial, antifungal, and antiviral effects at low concentrations through the photocatalytic activity and coordination of rare earth ions, and at the same time have excellent biocompatibility and environmental friendliness, and have been widely used in medical, food packaging, textiles and other fields. For example, in the surface coating of medical devices, rare earth antibacterial agents can significantly reduce the risk of cross - infection; in functional textiles, they can improve the hygienic protection performance. However, single - function rare earth antibacterial materials are difficult to meet the multiple protection requirements. In the medical field, surgical gowns, protective masks, etc. need to resist pathogenic microorganisms and ultraviolet radiation at the same time; products such as sunscreen clothes and sun hats require the material to provide efficient ultraviolet blocking ability on the basis of antibacterial.

[0003] In the prior art, rare earth oxides or rare earth salts are prone to agglomeration in the composite material matrix, forming aggregates with larger sizes. The agglomeration of rare earth particles will significantly reduce their specific surface area, reduce the contact opportunity with target substances (such as bacteria, etc.), and lead to a decrease in the utilization rate of active sites. Aggregates may become stress concentration points in the composite material, reducing the mechanical properties of the material. In addition, in rare earth composite materials, there are often interfacial defects or phase separation phenomena between the rare earth component and the matrix material, resulting in non - uniform internal structure of the material. Non - uniform structure will cause uneven distribution of internal stress or energy when the composite material is stressed, illuminated, or heated, thus triggering local failure, which may lead to bacterial residues in some areas and the formation of drug - resistant colonies. At the same time, in actual preparation, there are often problems of poor functional synergy. The antibacterial function and ultraviolet - resistant function of rare earth may not be synergistically enhanced due to the mismatch of electronic structures. Summary of the Invention

[0004] In order to solve the problems mentioned in the above background art, the present invention provides a rare earth antibacterial and ultraviolet - resistant composite material and a preparation method thereof.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions: A preparation method of a rare earth antibacterial and ultraviolet - resistant composite material, comprising the following steps: Lanthanum oxide is added to a 1 - 2 mol / L dilute nitric acid solution, and heated and stirred at 60 - 80 °C until completely dissolved to obtain a lanthanum ion solution. Calcium nitrate tetrahydrate and the lanthanum ion solution are added to deionized water to prepare solution A. Ammonium hydrogen phosphate and a polymer carrier are added to deionized water to prepare solution B. Under magnetic stirring, solution B is slowly added dropwise to solution A to obtain a suspension. The pH value is adjusted, and it is stirred in an oil bath for 6 - 8 h and left to age at room temperature for 24 - 36 h. The precipitate is filtered, washed, and dried to obtain the rare earth antibacterial and ultraviolet - resistant composite material.

[0006] Further, the polymer carrier is prepared by the following steps: Under nitrogen protection, divinylbenzene and 2 - vinyl - 4,6 - diamino - 1,3,5 - triazine are added to a reactor pre - filled with anhydrous ethanol, and stirred at a controlled temperature until completely dissolved. Azobisisobutyronitrile is added, and the temperature is raised and stirred for a reaction time of 6 - 8 h. After the reaction, it is centrifuged at a speed of 4000 rpm for 10 min, washed three times alternately with deionized water and ethanol, and dried to a constant weight to obtain the polymer carrier.

[0007] Further, the solid - liquid ratio of lanthanum oxide to the dilute nitric acid solution is 1 g:(1.5 - 2) mL. The 1 - 2 mol / L dilute nitric acid solution is prepared by diluting concentrated nitric acid (mass concentration 65%) and deionized water in a volume ratio of 1:(4.5 - 2.3). The mass ratio of calcium nitrate tetrahydrate, the lanthanum ion solution, and deionized water is (9.6 - 12):(4 - 6):100.

[0008] Further, the mass ratio of ammonium hydrogen phosphate, the polymer carrier, and deionized water is (3.2 - 3.4):(1.5 - 2.5):100.

[0009] Further, the pH value is adjusted to 9 - 10 with concentrated ammonia water, the temperature of the oil bath is 70 - 75 °C, and the stirring speed is 100 - 200 rpm.

[0010] Further, the mass ratio of divinylbenzene, 2 - vinyl - 4,6 - diamino - 1,3,5 - triazine, anhydrous ethanol, and azobisisobutyronitrile is (5.1 - 5.7):(2.8 - 3.2):(78 - 85):(0.1 - 0.12).

[0011] Further, the temperature during the controlled - temperature stirring is 24 - 26 °C, the stirring speed is 300 - 400 rpm, the temperature during the temperature - raising reaction is 68 - 72 °C, and the stirring speed is 500 - 600 rpm.

[0012] According to another aspect of the present invention, there is provided a rare earth antibacterial and ultraviolet - resistant composite material prepared by the above - mentioned preparation method.

[0013] The beneficial effects of the present invention: 1. In the technical solution of the present invention, a three-dimensional cross-linked network is constructed with 2-vinyl-4,6-diamino-1,3,5-triazine as the functional monomer. The amino groups and triazine ring nitrogen atoms in this monomer can form coordination bonds with rare earth ions, enabling the rare earth to be anchored on the polymer backbone in the form of monodispersion or nano-clusters, reducing the phenomenon of physical aggregation. At the same time, covalent bonding strengthens the interfacial bonding between the rare earth and the matrix, avoiding the risk of local failure caused by phase separation.

[0014] 2. In the technical solution of the present invention, the triazine ring in the polymer carrier absorbs short-wave ultraviolet rays through the conjugated π-electron system, while the rare earth ions absorb long-wave ultraviolet rays through electronic transitions, forming an ultraviolet shielding in the full wavelength range. At the same time, the synergistic coordination effect between the amino groups and the rare earth ions can disrupt the integrity of the bacterial cell membrane and achieve a dual antibacterial mechanism by interfering with the DNA replication of microorganisms, enabling the material to simultaneously achieve high-efficiency antibacterial and broad-spectrum ultraviolet resistance functions without adding other components.

[0015] 3. In the technical solution of the present invention, the high cross-linking density of the three-dimensional cross-linked network endows the material with excellent mechanical strength and thermal stability, which can resist the structural collapse caused by external stress and temperature changes. At the same time, the amino groups in the carrier have pH-responsive characteristics, and can dynamically adjust the pore size in an acidic environment (such as the site of bacterial infection) to achieve the targeted release of antibacterial components, while maintaining the structural compactness under neutral conditions to reduce non-specific loss, ensuring long-term antibacterial activity and avoiding the rapid failure of active ingredients in traditional materials.

[0016] 4. In the technical solution of the present invention, the polymer backbone is constructed from biocompatible monomers, and the degradation products are non-toxic and harmless. The rare earth components are fixed in the carrier through chemical bonding, effectively inhibiting ion dissolution. The calcium phosphate-based mineral layer in-situ generated on the material surface simulates the natural biomineralization process, not only enhancing the compatibility with biological tissues, but also improving the wear resistance and weather resistance of the material through the biomimetic mineralization strategy. Compared with traditional silver-containing or organic antibacterial agents, this system avoids the risks of heavy metal accumulation and ecological toxicity. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the following will briefly introduce the drawings required for the description of the embodiments or the prior art. Obviously, the drawings in the following description are only some embodiments of the present invention. For those of ordinary skill in the art, without creative efforts, other drawings can be obtained based on these drawings.

[0018] Figure 1 It is the antibacterial evaluation effect diagram of different rare earth antibacterial materials of the present invention against Escherichia coli; Figure 2Antibacterial evaluation effect diagram of different rare earth antibacterial materials of the present invention against Staphylococcus aureus; Figure 3 Ultraviolet spectrogram of different rare earth antibacterial materials and lanthanum oxide of the present invention. Detailed implementation manners

[0019] The technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts shall fall within the protection scope of the present invention.

[0020] Unless otherwise specified, the raw materials used in the present invention are all conventional products purchased from the market.

[0021] Preparation Example 1: The polymer carrier is prepared by the following steps: Under nitrogen protection, 5.1 g of divinylbenzene and 2.8 g of 2-vinyl-4,6-diamino-1,3,5-triazine are added to a reactor pre-filled with 78 g of absolute ethanol, the temperature is controlled at 24 °C, and the mixture is stirred at a speed of 300 rpm until completely dissolved. 0.1 g of azobisisobutyronitrile is added, the temperature is raised to 68 °C, and the mixture is stirred at a speed of 500 rpm for a reaction time of 6 h. After the reaction is completed, it is centrifuged at a speed of 4000 rpm for 10 min, washed three times alternately with deionized water and ethanol, and dried to constant weight to obtain the polymer carrier.

[0022] Preparation Example 2: The polymer carrier is prepared by the following steps: Under nitrogen protection, 5.4 g of divinylbenzene and 3 g of 2-vinyl-4,6-diamino-1,3,5-triazine are added to a reactor pre-filled with 80 g of absolute ethanol, the temperature is controlled at 25 °C, and the mixture is stirred at a speed of 350 rpm until completely dissolved. 0.11 g of azobisisobutyronitrile is added, the temperature is raised to 70 °C, and the mixture is stirred at a speed of 550 rpm for a reaction time of 7 h. After the reaction is completed, it is centrifuged at a speed of 4000 rpm for 10 min, washed three times alternately with deionized water and ethanol, and dried to constant weight to obtain the polymer carrier.

[0023] Preparation Example 3: The polymer carrier is prepared by the following steps: Under nitrogen protection, 5.7 g of divinylbenzene and 3.2 g of 2-vinyl-4,6-diamino-1,3,5-triazine were added to a reactor pre-filled with 85 g of absolute ethanol. The temperature was controlled at 26 °C and stirred at a speed of 400 rpm until completely dissolved. 0.12 g of azobisisobutyronitrile was added, and the temperature was raised to 72 °C. Stirred at a speed of 600 rpm for 8 h. After the reaction, centrifuged at a speed of 4000 rpm for 10 min, washed alternately with deionized water and ethanol three times, and dried to a constant weight to obtain a polymer support.

[0024] Example 1: A preparation method of a rare earth antibacterial and ultraviolet ray-proof composite material, comprising the following steps: 10 g of lanthanum oxide was added to 15 mL of 1 mol / L dilute nitric acid solution, heated and stirred at 60 °C until completely dissolved to obtain a lanthanum ion solution. 9.6 g of calcium nitrate tetrahydrate and 4 g of the lanthanum ion solution were added to 100 g of deionized water to prepare solution A. 3.2 g of diammonium hydrogen phosphate and 1.5 g of the polymer support prepared in Preparation Example 1 were added to 100 g of deionized water to prepare solution B. Under magnetic stirring, solution B was slowly added dropwise to solution A to obtain a suspension. The pH value was adjusted to 9 with 25% concentrated ammonia water by mass concentration, stirred at a speed of 100 rpm in an oil bath at 70 °C for 6 h, allowed to stand and age at room temperature for 24 h, filtered to obtain a precipitate, and the obtained precipitate was washed alternately with deionized water and ethanol three times to remove other soluble substances, dried to a constant weight to obtain a rare earth antibacterial and ultraviolet ray-proof composite material, denoted as HA / 4 g-La2O3.

[0025] Example 2: A preparation method of a rare earth antibacterial and ultraviolet ray-proof composite material, comprising the following steps: 10 g of lanthanum oxide was added to 18 mL of 1.5 mol / L dilute nitric acid solution, heated and stirred at 70 °C until completely dissolved to obtain a lanthanum ion solution. 10 g of calcium nitrate tetrahydrate and 5 g of the lanthanum ion solution were added to 100 g of deionized water to prepare solution A. 3.3 g of diammonium hydrogen phosphate and 2 g of the polymer support prepared in Preparation Example 2 were added to 100 g of deionized water to prepare solution B. Under magnetic stirring, solution B was slowly added dropwise to solution A to obtain a suspension. The pH value was adjusted to 9.5 with 26% concentrated ammonia water by mass concentration, stirred at a speed of 150 rpm in an oil bath at 72 °C for 7 h, allowed to stand and age at room temperature for 30 h, filtered to obtain a precipitate, and the obtained precipitate was washed alternately with deionized water and ethanol three times to remove other soluble substances, dried to a constant weight to obtain a rare earth antibacterial and ultraviolet ray-proof composite material, denoted as HA / 5 g-La2O3.

[0026] Example 3: A preparation method of a rare earth antibacterial and ultraviolet ray-proof composite material, comprising the following steps: 10 g of lanthanum oxide was added to 20 mL of 2 mol / L dilute nitric acid solution, and heated and stirred at 80 °C until completely dissolved to obtain a lanthanum ion solution. 12 g of calcium nitrate tetrahydrate and 6 g of the lanthanum ion solution were added to 100 g of deionized water to prepare solution A. 3.4 g of diammonium hydrogen phosphate and 2.5 g of the polymer carrier prepared in Preparation Example 3 were added to 100 g of deionized water to prepare solution B. Under magnetic stirring, solution B was slowly added dropwise to solution A to obtain a suspension. The pH value was adjusted to 10 with 28% concentrated ammonia water, and stirred at a speed of 200 rpm in an oil bath at 75 °C for 8 h, and left to stand and age at room temperature for 36 h. The precipitate was obtained by filtration. The obtained precipitate was washed alternately with deionized water and ethanol three times to remove other soluble substances, and dried to constant weight to obtain a rare earth antibacterial and ultraviolet-proof composite material, denoted as HA / 6g-La2O3.

[0027] Comparative Example 1: 9.6 g of calcium nitrate tetrahydrate was added to 100 g of deionized water to prepare solution A. 3.2 g of diammonium hydrogen phosphate and 1.5 g of the polymer carrier prepared in Preparation Example 1 were added to 100 g of deionized water to prepare solution B. Under magnetic stirring, solution B was slowly added dropwise to solution A to obtain a suspension. The pH value was adjusted to 9 with concentrated ammonia water, and stirred at a speed of 100 rpm in an oil bath at 70 °C for 6 h, and left to stand and age at room temperature for 24 h. The precipitate was obtained by filtration. The obtained precipitate was washed alternately with deionized water and ethanol three times to remove other soluble substances, and dried to constant weight, denoted as HA.

[0028] 200 mL of distilled water was measured with a measuring cylinder and poured into a 250 mL reagent bottle. 3.6 g of LB broth medium was weighed with an analytical electronic balance and added and mixed evenly. After sterilization at 126 °C for 3 h in a high-temperature high-pressure steam sterilizer, it was ready for use to obtain LB liquid medium.

[0029] 400 mL of distilled water was measured with a measuring cylinder and poured into a 450 mL reagent bottle. 7.2 g of LB broth medium and 6.0 g of agar powder were weighed with an analytical electronic balance. The above-mentioned weighed reagents were added and mixed evenly. After sterilization at 126 °C for 3 h in a high-temperature high-pressure steam sterilizer, when the medium cooled to 45 °C, 15 mL of the medium was aspirated with an electric pipette and poured into a disposable sterile petri dish, and left to stand and solidify to obtain LB solid medium.

[0030] Take 2 12 mL bacterial culture tubes, each add 4.5 mL of LB liquid medium, and then add 0.5 mL of 10 7 CFU / mL Staphylococcus aureus (No.: ATCC 25922) and Escherichia coli (No.: ATCC 29213), and dilute to 10 6CFU / mL of Staphylococcus aureus and Escherichia coli were recorded as the blank control group. Then, another 8 12-mL bacterial culture tubes were taken. Among them, 4 test tubes were for the Staphylococcus aureus group, each added with 4.5 mL of LB liquid medium, 0.1 g of the rare earth antibacterial and ultraviolet-proof composite material sample prepared in Examples 1-3, and 0.5 mL of 10 6 CFU / mL of Staphylococcus aureus. The other 4 test tubes were for the Escherichia coli group, each added with 4.5 mL of LB liquid medium, 0.1 g of the rare earth antibacterial and ultraviolet-proof composite material sample prepared in Examples 1-3, and 0.5 mL of 10 6 CFU / mL of Escherichia coli. They were placed in a constant temperature oscillator (37°C, 200 rpm) and shaken. The samples were grouped and placed in disposable petri dishes, irradiated under an ultraviolet lamp for 30 min for sterilization, and reserved. Another test tube was taken and added with 4.5 mL of LB liquid medium, 0.1 g of HA prepared in Comparative Example 1, and 0.5 mL of 10 6 CFU / mL of Staphylococcus aureus, and the same for Escherichia coli.

[0031] 20 μL of the bacterial liquid dilution was aspirated, evenly coated on the LB solid medium using a glass spreader, placed in a constant temperature oscillator (37°C, 200 rpm) and shaken for 24 h, taken out, photographed, and the number of colonies was recorded. The antibacterial rate was calculated as antibacterial rate = (1 - concentration of bacterial liquid in the experimental group / concentration of bacterial liquid in the control group) × 100%. The evaluation results were as Figure 1 and Figure 2 shown. The colony counting results are shown in Table 1 and Table 2: Table 1. Antibacterial results of Escherichia coli

[0032] Table 2. Antibacterial results of Staphylococcus aureus

[0033] Note: The number of colonies is the colony counting result under the corresponding treatment conditions of each group. Under the optimal culture environment, if there is still no colony growth, it proves that the antibacterial effect of the sample is obvious.

[0034] As Figure 1-2 and shown in Table 1-2, the sample of Example 3 had the best antibacterial effect on Escherichia coli, and the number of colonies on the plate was 26. The sample of Example 1 had the best antibacterial effect on Staphylococcus aureus, and the number of colonies on the plate was 0.

[0035] As Figure 3As shown, each sample was ground to less than 200 mesh, mixed with KBr at a mass ratio of 1:100, and pressed into tablets. Then, it was scanned using a UV-visible spectrophotometer in the wavelength range of 200 - 800 nm at a scanning rate of 240 nm / min. The UV absorption wavelength of HA is 250 nm, that of lanthanum oxide is 259 nm, and those of HA / 4g-La2O3, HA / 5g-La2O3, and HA / 6g-La2O3 are 275 nm, 289 nm, and 300 nm respectively, indicating that the light absorption range is further expanded.

[0036] The excellent antibacterial effect (99.9%) of Example 3 (HA / 5g-La2O3) against Escherichia coli may be due to a higher La 3+ loading amount. La 3+ induces membrane rupture by disrupting the ζ-potential balance of the lipid bilayer of the bacterial membrane, and can penetrate into the cell at high concentrations to interfere with DNA replication. Staphylococcus aureus (Gram-positive bacteria), due to its thicker peptidoglycan layer, may have higher resistance to La 3+ penetration. A lower concentration is required to achieve rapid inactivation through surface adsorption, so Example 1 shows a 100% antibacterial rate against it. The pH-responsive property of the amino groups in the carrier is protonated in a weakly acidic environment, dynamically expanding the pores to promote the targeted release of La 3+ . The pH of the Escherichia coli living environment (about 6.5) is closer to the amino pKa value than that of Staphylococcus aureus (about 7.2), accelerating the release of La 3+ and forming a concentration-dependent bactericidal difference.

[0037] The UV spectrum shows a red shift in the absorption edge of the composite material. For HA / 6g-La2O3, it reaches 300 nm, which is due to the energy level coupling of the π→π* transition (short-wave absorption) of the triazine ring and the 4f→5d transition (long-wave absorption) of La 3+ . The introduction of La 3+ reduces the band gap of the material, broadening the light response range to the entire UVA-UVB band. An electron transport channel is formed between the polymer carrier and La2O3 through an N→La coordination bond, promoting the separation efficiency of photo-generated electrons and holes. While enhancing the UV absorption, it may generate reactive oxygen species to assist in antibacterial, forming a dual bactericidal path of photocatalysis-ion release.

[0038] In summary, the composite materials prepared in Examples 1 - 3 have good antibacterial and UV protection properties.

[0039] In the description of the specification, the descriptions referring to terms such as "preparation example", "embodiment", "each embodiment", etc. mean that the specific features, structures, materials or characteristics described in connection with that embodiment or preparation example are included in at least one embodiment or preparation example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or preparation example. Moreover, the specific features, structures, materials or characteristics described can be combined in a suitable manner in any one or more embodiments or preparation examples.

[0040] As mentioned above, only the preferred specific embodiments of the present invention are described, but the protection scope of the present invention is not limited thereto. Any person skilled in the art within the technical scope disclosed by the present invention, according to the technical solution and inventive concept of the present invention, making equivalent substitutions or changes, should be covered by the protection scope of the present invention.

Claims

1. A preparation method of a rare earth antibacterial and ultraviolet - resistant composite material, characterized in that, It includes the following steps: Add calcium nitrate tetrahydrate and lanthanum ion solution into deionized water to prepare solution A, add diammonium hydrogen phosphate and polymer carrier into deionized water to prepare solution B. Under magnetic stirring, slowly drop solution B into solution A to obtain a suspension. Adjust the pH value, stir in an oil bath for 6 - 8 h, stand and age at room temperature for 24 - 36 h, filter to obtain a precipitate, wash and dry to obtain the rare earth antibacterial and anti-ultraviolet composite material.

2. The preparation method of a rare earth antibacterial and ultraviolet resistant composite material according to claim 1, characterized in that, The polymer carrier is prepared through the following steps: Under nitrogen protection, add divinylbenzene and 2-vinyl-4,6-diamino-1,3,5-triazine into a reactor pre-filled with absolute ethanol, control the temperature and stir until completely dissolved, add azobisisobutyronitrile, raise the temperature and stir for a reaction time of 6 - 8 h. After the reaction ends, centrifuge, wash and dry to obtain the polymer carrier.

3. The preparation method of a rare earth antibacterial and ultraviolet resistant composite material according to claim 1, characterized in that, The mass ratio of calcium nitrate tetrahydrate, lanthanum ion solution and deionized water is (9.6 - 12) : (4 - 6) :

100.

4. The preparation method of a rare earth antibacterial and ultraviolet resistant composite material according to claim 1, characterized in that, The mass ratio of diammonium hydrogen phosphate, polymer carrier and deionized water is (3.2 - 3.4) : (1.5 - 2.5) :

100.

5. The preparation method of a rare earth antibacterial and ultraviolet-proof composite material according to claim 1, characterized in that, After obtaining the suspension, adjust the pH value to 9 - 10 with concentrated ammonia water, the temperature of the oil bath is 70 - 75 °C, and the stirring speed is 100 - 200 rpm.

6. The preparation method of a rare earth antibacterial and ultraviolet-proof composite material according to claim 2, characterized in that, The mass ratio of divinylbenzene, 2-vinyl-4,6-diamino-1,3,5-triazine, absolute ethanol and azobisisobutyronitrile is (5.1 - 5.7) : (2.8 - 3.2) : (78 - 85) : (0.1 - 0.12).

7. The preparation method of a rare earth antibacterial and ultraviolet-proof composite material according to claim 2, characterized in that, When controlling the temperature and stirring, the temperature is 24 - 26 °C, and the stirring speed is 300 - 400 rpm. When raising the temperature for the reaction, the temperature is 68 - 72 °C, and the stirring speed is 500 - 600 rpm.

8. A rare earth antibacterial and anti-ultraviolet composite material prepared by the preparation method according to any one of claims 1 - 7.

Citation Information

Patent Citations

  • Cyanate ester polymer

    CN101283022A

  • Antibacterial property resin composite material and preparation method thereof

    CN103059549A

  • Lanthanum-containing rare earth functional antibacterial fiber and preparation method thereof

    CN118685879A

  • Rare earth doped zinc oxide functional polyamide polymer as well as preparation method and application thereof

    CN118702911A

  • Water absorptive gel for recovering metal ion

    JP2017031440A

Cited By

  • Composite sponge for seawater desalination and preparation method thereof

    CN120775252A